2022
DOI: 10.1002/jso.27009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing oncoplastic breast reduction with immediate symmetry surgery to standard breast reduction surgery: Are postoperative complications worse?

Abstract: Introduction Oncoplastic breast reduction mammoplasty (ORM) is an excellent treatment option for women with breast cancer and macromastia undergoing breast conservation therapy. Here, we aim to better understand the risks associated with ORM compared to standard reduction mammoplasty (SRM). Methods A retrospective chart review was performed of patients undergoing ORM or SRM from 2015 to 2021. Primary outcomes included the occurrence of major or minor postoperative complications in the two groups and delays to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Nine articles were identified that met inclusion criteria, representing 1715 patients (Table 1) with surgery occurring between 1995 and 2020. [11][12][13][14][15][16][17][18][19] Reported mean follow-up ranged from 9.4 to 84 months. Mean patient age ranged from 51.9 to 59.6 years and mean body mass index had a range of 24.2-33.5 kg/m 2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles were identified that met inclusion criteria, representing 1715 patients (Table 1) with surgery occurring between 1995 and 2020. [11][12][13][14][15][16][17][18][19] Reported mean follow-up ranged from 9.4 to 84 months. Mean patient age ranged from 51.9 to 59.6 years and mean body mass index had a range of 24.2-33.5 kg/m 2 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…OPS is a safe and accepted option for breast cancer surgery 15,16 . As such, efforts should be made to improve accessibility to oncoplastic techniques in the management of breast cancer patients in the United States 17 .…”
Section: Discussionmentioning
confidence: 99%
“…OPS is a safe and accepted option for breast cancer surgery. 15,16 As such, efforts should be made to improve accessibility to oncoplastic techniques in the management of breast cancer patients in the United States. 17 As societies begin to investigate training surgeons in OPS, learning curve studies such as ours demonstrating results are important in guiding teaching programs.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients undergoing immediate oncoplastic breast reduction are usually older and with a higher number of comorbidities compared to standard reduction mammoplasty, they show a similar safety profile without significant delays to adjuvant therapy [16]. The same is not verified when comparing immediate and delayed breast therapeutic reduction complications when radiotherapy is performed.…”
Section: Discussionmentioning
confidence: 99%